Symptom documentation and intervention provision for symptom control in children receiving cancer treatments. (March 2019) - Hyslop, Shannon; Davis, Hailey; Duong, Nathan; Loves, Robyn; Schechter, Tal; Tomlinson, Deborah; Tomlinson, George A.; Dupuis, L. Lee; Sung, Lillian
Abstract: Background: Objectives were to describe the proportion of bothersome symptoms self-reported using the Symptom Screening in Pediatrics Tool (SSPedi) documented in the medical records and associated with an intervention. Methods: Eligible respondents were inpatients aged 8–18 years receiving cancer treatments and expected to be in hospital or clinic three days later. Children self-reported symptom bother using SSPedi. We evaluated symptom documentation and interventions in the medical records proximal to SSPedi administration. Results: There were 168 children included. Symptoms rated as at least 'a lot' bother were documented in the medical record less than 60% of the time for 12 of 15 symptoms. Of these symptoms, the most infrequently documented symptoms were problems with thinking or remembering things (0%), changes in how your body or face look (4.8%), changes in taste (7.7%) and tingly or numb hands or feet (11.1%). Intervention provision for symptoms rated as 'a lot' bother occurred less than 60% of the time for 10 of 15 symptoms. Of these symptoms, the most infrequently treated were thinking or remembering things (0%), changes in how your body or face look (0%), tingly or numb hands or feet (0%), changes in taste (0%), diarrhoea (0%) and feeling tired (1.6%). Conclusions: Documentation of symptoms and intervention provision were generally infrequent. Symptoms that were almost never documented or treated included problems with cognition, body image, taste changes and peripheral neuropathy. Future efforts should incorporate symptom screening into routine care and facilitate symptom management by improving access to evidence-based clinical practice guidelines. Highlights: Documentation of symptoms and provision of interventions was generally poor. Most bothersome symptoms were documented less than 60% of the time. Interventions were provided less than 60% of the time for most bothersome symptoms.